In vitro Antibacterial Activity of Quercetin Containing Extract from Hibiscus Sabdariffa L. Calyxes - Anh, Do Thi Hai; Hoang, Le Huy; Shihavong, Kitsamone; Uy, Nguyen Thai; Huy, Nguyen Quang (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Hibiscus sabdariffa L. has been used traditionally as food and in herbal medicine because its calyxes are rich of flavonoids source especially quercetin and anthocyanin. In addition, its antibacterial activity is implied to be helpful for human health even at the low concentration. In this study, we investigated the in vitro antibacterial activity and quantified the free quercetin in hibiscus extract using sensitive and reliable methods such as agar disk diffusion, HPTLC and LC-MS/MS. The results indicated that crude methanol extract of hibiscus calyxes had strong antibacterial activity. The total phenolic and flavonoid contents of hibiscus calyxes were 25.07 mg GAE/g DW and 29.96 mg QE/g DW, respectively. From methanol hibiscus extract, quercetin was determined by using HPTLC and LC-MS/MS methods. There was presence of quercetin aglycone in one fraction (which showed highest antibacterial activity) at the concentration of 11.3 ng/ml. This study provided useful information in using reliable and sensitive methods for screening and determining antibacterial activity of free quercetin at the low concentration based on any plant raw material. Keywords: Quercetin, Hibiscus sabdariffa L., antibacterial, HPTLC.